GROUND MAGNETIC STUDY OF GEOLOGICAL STRUCTURES AND MINERALIZATION IN AWO AREA, NEAR EDE, SOUTH WESTERN NIGERIA - Igboama, Wilfred N.; Aroyehun, M. T.; Olowofela, J. A.; Hammed, O. S.; Ugwu, N. U. (FUDMA JOURNAL OF SCIENCES, 2024)
Ground magnetic study was carried out in Awo area, Osun State, Nigeria. The area lies within latitudes 70 44¢N and 70 48¢N and longitudes 4020¢E and 4024¢E in Southwestern part of Nigeria. The study focused on delineation of geological structures like: faults, fractures and possible minerals in the area.  GM122 Proton Precession magnetometer was employed and 16 traverses were executed along roads and pathways for ease of labour and adequate coverage at spacing interval of 10 m between station points. Isolation of residuals was carried out to get magnetic residual intensity values that were plotted against station points using Microsoft excel. The quantitative interpretation was done using “half-slope” and “straight-slope” methods, as they are easy to use, fast and cost effective. The range of overburden thickness to the top of magnetized body obtained was between 2.50 and 30.00 metres. Qualitatively, the results obtained were used to delineate inflection points, contacts, fractures and faults by plotting 2-D and 3-D contour maps using Sufer applications. The graphs indicate geological structures, rock types and magnetic characteristics of minerals. The low magnetic values suggest presence of faults and fractures in the area while the high relative intensity values indicate deep structures, which may be due to block faulting. These findings have significant implications for mineral exploration in the region, particularly for identifying structurally controlled deposits. Rock types including banded gneiss and granite gneiss with pegmatite veins and economically valuable minerals such as tantalite, barite, quartz, mica and gravel were found in the area.